(untitled) (Jurnal Proaksi, 2021)
This study aims to examine the effect of accountability, transparency, and social participation on the management of village fund allocations in villages in the Kalitidu sub-district, Bojonegoro district. The subjects of this research are village officials who directly manage the allocation of village funds. The method of determining the sample used purposive sampling technique, so that a sample of 72 village officials was obtained. Data were collected through a questionnaire. Data were analyzed using SEM PLS with WarpPLS 7.0 software program. The results of the study prove that accountability, transparency, and social participation had a positive and significant impact on the management of village fund allocations.